In Vitro Design and Evaluation of Phage Cocktails Against Aeromonas salmonicida - Chen, Ling; Yuan, Shengjian; Liu, Quan; Mai, Guoqin; Yang, Jinfang; Deng, Deng; Zhang, Bingzhao; Liu, Chenli; Ma, Yingfei (Frontiers in Microbiology, 2018)
As an alternative approach against multidrug-resistant bacterial infections, phages are now being increasingly investigated as effective therapeutic agents. Here, aiming to design an efficient phage cocktail against A. salmonicida infections, we isolated and characterized five lytic A. salmonicida phages, AS-szw, AS-yj, AS-zj, AS-sw, and AS-gz. The results of morphological and genomic analysis suggested that all these phages are affiliated to the T4virus genus of the Caudovirales order. Their heterogeneous lytic capacities against A. salmonicida strains were demonstrated by experiments. A series of phage cocktails were prepared and investigated in vitro. We observed that the cocktail combining AS-gz and AS-yj showed significantly higher antimicrobial activity than other cocktails and individual phages. Given the divergent genomes between the phages AS-yj and AS-gz, our results highlight that the heterogeneous mechanisms that phages use to infect their hosts likely lead to phage synergy in killing the host. Conclusively, our study described a strategy to develop an effective and promising phage cocktail as a therapeutic agent to combat A. salmonicida infections, and thereby to control the outbreak of relevant fish diseases. Our study suggests that in vitro investigations into phages are prerequisite to obtain satisfying phage cocktails prior to application in practice.